Autonomic Nervous System Mediates the Hypotensive Effects of Aqueous and Residual Methanolic Extracts of Syzygium polyanthum (Wight) Walp. var. polyanthum Leaves in Anaesthetized Rats - Ismail, A.; Mohamed, M.; Sulaiman, S. A.; Wan Ahmad, W. A. N. (Hindawi Publishing Corporation, 2013)
Syzygium polyanthum (Wight) Walp. var. polyanthum leaves are consumed as a traditional Malay treatment of hypertension. This study investigates hypotensive potential of aqueous (AESP) and residual methanolic (met-AESP) extracts of S. polyanthum leaves and possible involvement of autonomic receptors. AESP and met-AESP (20 to 100mg/kg) were intravenously administered into anaesthetized Wistar-Kyoto (WKY) and spontaneously hypertensive (SHR) rats. Blood pressure and heart were monitored for 20 min. AESP and met-AESP induced significant dose-dependent hypotension, but only 100mg/kg AESP caused mild bradycardia (